Influence of nutrition and physical activity in teaching processes learning: a look from evidence for transformation (Revista horizonte, 2021)
The  transformation  processes  suffered  in  Chile  due  to  modernization  have  brought  with  it  problems associated with food, nutrition  and physical activity aspects. These factors and bad habits  such as sedentary lifestyle,  impact  on  health  problems,  epidemiological  and  aspects  related  to  the  performance  or  learning  of the school population. The challenges of national country policy are focused on reducing economic gaps and achieving  equity  in  educational  issues  as  promoters  of  social  transformation.  The  investigation  of  teaching methods  to improve  the  learning  or  academic  performance  of  children  is important.  Research  focused  on food,  nutrition  and  physical  activity  aspects  have  shown  their  influence  on  the willingness  to  study  and modifier  of  neuronal  chemical  environments  that  favor  cognitive processes  related  to  learning.  The articulation  of  variables  can  be  helpful  for  the transformation  process.